Homens imprudentemente poéticos: alteridade e criação literária em Valter Hugo Mãe - Garcia, Sílvia Cristina (2019)
This dissertation has as its corpus of investigation the novel Homens imprudentemente poéticos, of 2016, published by the Angolan writer Valter Hugo Mãe. The objective of the work is to highlight the way the narrator constructs the characters, as well as the artifices used to awaken the reader in relation to the narrative poeticity. The objective extends also towards the understanding of intersubjectivity – a critical question to mankind and, in particular, to literary creation. The theoretical foundation relies on the concepts of otherness, according to Emmanuel Lévinas, and outridade, by Octavio Paz; of the beautiful and sublime, of Friedrich Schiller; of beauty, in Plotino; of the grotesque in Wolfgang Kayser; of estrangement, by Vitor Chklovski; and performance in Reading, in Paul Zumthor. Finally,the postulates of Octavio Paz on poetic creation are alto used as theoretical support. To complete the theoretical approach, it is also used the universe of phantasmagoria and the fantastic, besides the dialogue between the East and the West, born from the thematic-cultural scenario, whose plot is set in Japan